PELATIHAN KEWIRAUSAHAAN PEMUDA BIDANG USAHA SERVIS ELEKTRONIK PROVINSI SUMATERA SELATAN - Gultom, Angga Wibowo; Anwar, Rani; Putriani, Dyah Ayu; Natalia, Titi Syahnaz; Herlina, Tati; Wulanda, Nourma; Rabiulkhri, Mailani; Tusri, Yudi (Nindikayla Institute, 2023)
South Sumatra Province has great and diverse youth potential, but many young people still experience difficulties in finding work or developing their own businesses. One of the promising business fields is electronic services, for this purpose the service activities aim to assist youth in developing businesses in the electronics service sector. The results of the training show that youth gain an understanding of the importance of building good relationships with customers by implementing online marketing as an effective promotional strategy while still not abandoning offline marketing strategies